A Case-Based Guide to Eye Pain Perspectives from Ophthalmology and Neurology - Lee, Michael S. (Springer International Publishing, 2018)
Diagnosing a patient with unexplained ocular pain can be time-consuming and difficult, but taking an anatomic approach and excluding causes along the way can aid in the diagnosis. This book provides the reader with a systematic evaluation plan for these cases, written and edited by leaders in the field. A Case-Based Guide to Eye Pain is written for both ophthalmologists and neuro-ophthalmologists since there are not enough neuro-ophthalmologists to treat the number of patients with unexplained ocular pain and general ophthalmologists are having to take on the diagnosis and treatment of these patients. Organized in an easy-to-use manner, each case covers the following key elements: the chief complaint, history of the present illness, the examination, assessment and plan, follow-up, alternate perspective, summary points, and key references. Tables are also available to help the reader rapidly sort through cases that may apply to a sign, symptom, historical feature, diagnostic test or treatment option. This allows the practitioner who has a patient with a particular concern to use the tables to identify a case discussion. Additionally, A Case-based Guide to Eye Pain includes an appendices with the general approach to eye pain and anatomy of the trigeminal pathway and its relation to eye pain.